Key Determinants of Channel Switching Intention During the Covid-19 Pandemic: Evidence from an Emerging Market - Tuncer, İlhami (International Journal of Contemporary Economics and Administrative Sciences, 2021)
The COVID-19 pandemic has become a global problem with its rapid spread to almost the whole world, impacting many areas, especially health. Therefore, the negative climate created by this pandemic is likely to affect consumers’ purchasing behavior. Therefore, this study aims to examine the relationships between perceived offline shopping risk, trust in offline stores, and perceived threat in relation to how this affects consumers’ channel switching intentions. For this purpose, data were obtained from 422 online survey participants and analyzed using structural equation modeling. The results show that trust in offline stores has a negative relationship with perceived offline shopping risk, and that perceived risk of offline shopping and perceived threat have a significant positive relationship with consumers’ channel switching intentions. These findings contribute to the development of understanding in relation to channel switching intentions in the retail sector. In addition, these findings provide retail managers and practitioners with practical insight into perceived risk, trust, perceived threat, and channel switching intentions during the COVID-19 pandemic.